Uji Daya Hambat Air Rebusan Daun Teh Hijau ( Camellia sinensis, L) Terhadap Kutu Air (Tinea pedis) - Elen Marlina; Eka Nurdianty Anwar (Jurnal Vokasi Kesehatan, 2022)
Green tea foliphenol catechins are hydroxylated phenols that can be toxic to microorganisms, these compounds form protein complexes and inhibit the work of enzymes that act on cell membranes so that they damage the microbial membrane. The aim of this study was to determine the most effective concentration of green tea leaf (Camellia sinensis, L) boiled water on the growth of the water flea fungus (Tinea pedis). This research was conducted at the Pathology Laboratory of the Harapan Bangsa Health Analyst Academy, Bengkulu on July 13-17, 2020. The sampling technique was simple random sampling and the inhibition zone was the diffusion method. In this study, the results obtained at 20% concentration obtained a clear zone with a diameter of 7 mm, 40% obtained a clear zone with a diameter of 7.3 mm, 60% obtained a clear zone with a diameter of 7.6 mm, 80% obtained a clear zone with a diameter of 9, 3 mm and 100% obtained clear zone with a diameter of 11.5 mm. The results of this study can be said that the boiled water of green tea leaves (Camellia sinensis, L) is most effective against the growth of the water flea fungus (Tinea pedis) at a concentration of 100% of 11.5 mm..